A case study: using social tagging to engage students in learning Medical Subject Headings. - Maggio LA; Bresnahan M; Flynn DB; Harzbecker J; Blanchard M; Ginn D (Journal of the Medical Library Association, 2009)
In exploring new ways of teaching students how to use Medical Subject Headings (MeSH), librarians at Boston University's Alumni Medical Library (AML) integrated social tagging into their instruction. These activities were incorporated into the two-credit graduate course, 'GMS MS 640: Introduction to Biomedical Information,' required for all students in the graduate medical science program. Hands-on assignments and in-class exercises enabled librarians to present MeSH and the concept of a controlled vocabulary in a familiar and relevant context for the course's Generation Y student population and provided students the opportunity to actively participate in creating their education. At the conclusion of these activities, students were surveyed regarding the clarity of the presentation of the MeSH vocabulary. Analysis of survey responses indicated that 46% found the concept of MeSH to be the clearest concept presented in the in-class intervention.